Odonates (Insecta: Odonata) associated with rice ecosystems in Sunwal municipality, central Nepal - Sharma, Manoj; Oli, Buddhi Ram (Journal of Natural History Museum, 2022)
This paper aims to list the odonates fauna associated with rice fields and to study their behaviour in Sunwal, Central Nepal. Research was conducted from June to November 2019 in a rice field by establishing three study plots of (50×50) m2 each. A total of 33 odonata species (11 damselflies and 22 dragonflies) from six families were recorded. Six of them were sporadic, while the rest were common. Territorial behaviour of Odonates was observed and the reproductive behavior of 11 species was thoroughly investigated. The copulatory period varied between species, ranging from two seconds to 49 minutes. Females attempted to mate up to three times. The second and third mating were both brief. Homing behaviour was observed in single species - Orthetrum sabina. In this research, we noticed odonates to be predatory as well as prey species.